Climate Change and Disasters: How Framing Affects Justifications for Giving or Withholding Aid to Disaster Victims. (January 2016) - Chapman, Daniel A.; Lickel, Brian
This research examined whether framing a natural disaster as the product of climate change impacts attitudes toward disaster victims and humanitarian relief. Participants ( n = 211) read an article about a famine caused by severe droughts, with one condition attributing the droughts to climate change and the other condition made no mention of climate change. All participants then responded to measures of justifications for or against providing aid, attitudes toward the possibility of donating, and climate change beliefs. As predicted, those high in climate change skepticism reported greater justifications for not helping the victims when the disaster was attributed to climate change. Additional moderated mediation analyses showed there was an indirect effect of climate change framing on attitudes toward donating through donation justifications.